Proceedings of the 5th ASEAN Conference on Psychology, Counselling, and Humanities (ACPCH 2019) 2020
DOI: 10.2991/assehr.k.200120.067
|View full text |Cite
|
Sign up to set email alerts
|

Family-Based Intervention to Manage Anxiety and Depression in Chronic Illness Patients

Abstract: Family is a small unit in a society that has its own system. Family members interact and help each other in their daily lives. When one of its family members suffers from a chronic illness, it is susceptible to get psychological problems such as anxiety and depression. The purpose of this study is to analyze the effectiveness of family-based interventions in dealing with psychological problems in patients with chronic diseases. This research is based on a literature review of articles and journals obtained fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
0
0
Order By: Relevance
“…Another study by Kemp, Mead and Fisher ( 2022 ) highlighted that strengthening and maintaining psychosocial support services remotely enhances treatment adherence. Additionally, Rahia ( 2019 ) indicated that family-based interventions are not only effective in accessing treatment but help to reduce anxiety and depression in PWCDs. In the heat of a crisis, the voice of the patient needs to be heard.…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Kemp, Mead and Fisher ( 2022 ) highlighted that strengthening and maintaining psychosocial support services remotely enhances treatment adherence. Additionally, Rahia ( 2019 ) indicated that family-based interventions are not only effective in accessing treatment but help to reduce anxiety and depression in PWCDs. In the heat of a crisis, the voice of the patient needs to be heard.…”
Section: Discussionmentioning
confidence: 99%